2020
DOI: 10.1155/2020/5238650
|View full text |Cite
|
Sign up to set email alerts
|

Acrocomia aculeata(Jacq.) Lodd. ex Mart. Leaves Increase SIRT1 Levels and Improve Stress Resistance

Abstract: Oxidative stress is a metabolic disorder linked with several chronic diseases, and this condition can be improved by natural antioxidants. The fruit pulp of the palm Acrocomia aculeata (Jacq.) Lodd. ex Mart. is widely used in the treatment of various illnesses, but as far as we know, there are no reports regarding the properties of its leaves. Thus, we aimed to evaluate the antioxidant activity of A. aculeata leaf extracts obtained with water (EA-Aa), ethanol (EE-Aa), and methanol (EM-Aa) solvents. The extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 75 publications
1
16
0
2
Order By: Relevance
“…A phytochemical study of A. totai leaves revealed a new chemical compound that inhibits cell growth, called "totaiol," potentially allowing for medicinal applications (Souza et al 2019a). Leaf extracts were found to exhibit antioxidant properties with low toxicity (Monteiro-Alfredo et al 2020). Da and Nunes et al (2018) reported that kernel and pulp oils show hypoglycemic effects.…”
Section: A Short History Of Acrocomia Researchmentioning
confidence: 99%
“…A phytochemical study of A. totai leaves revealed a new chemical compound that inhibits cell growth, called "totaiol," potentially allowing for medicinal applications (Souza et al 2019a). Leaf extracts were found to exhibit antioxidant properties with low toxicity (Monteiro-Alfredo et al 2020). Da and Nunes et al (2018) reported that kernel and pulp oils show hypoglycemic effects.…”
Section: A Short History Of Acrocomia Researchmentioning
confidence: 99%
“…and economic importance (for cooking, biodiesel, and the cosmetic industry) [ 11 ]. Its carotenoid-rich fruit pulp was suggested to have beneficial effects on the treatment of respiratory diseases, as analgesic and laxative [ 12 ] and also in decreasing serum cholesterol and glucose levels [ 13 ]. Recently, our group proved the antioxidant potential of its leaves and the relevant chemical composition, mostly of vanillic, caffeic, ferulic and gallic acid, rutin and quercetin [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of metabolically active cells was performed using resazurin colorimetric assay [ 40 ]. Briefly, Cos-7 cells were seeded and allowed to stabilise in 96-well plates at a density of 8 × 10 4 cells/mL.…”
Section: Methodsmentioning
confidence: 99%